Engineering biosynthesis of high-value compounds in photosynthetic organisms. (18th August 2017) - O'Neill, Ellis C.; Kelly, Steven
Abstract: The photosynthetic, autotrophic lifestyle of plants and algae position them as ideal platform organisms for sustainable production of biomolecules. However, their use in industrial biotechnology is limited in comparison to heterotrophic organisms, such as bacteria and yeast. This usage gap is in part due to the challenges in generating genetically modified plants and algae and in part due to the difficulty in the development of synthetic biology tools for manipulating gene expression in these systems. Plant and algal metabolism, pre-installed with multiple biosynthetic modules for precursor compounds, bypasses the requirement to install these pathways in conventional production organisms, and creates new opportunities for the industrial production of complex molecules. This review provides a broad overview of the successes, challenges and future prospects for genetic engineering in plants and algae for enhanced or de novo production of biomolecules. The toolbox of technologies and strategies that have been used to engineer metabolism are discussed, and the potential use of engineered plants for industrial manufacturing of large quantities of high-value compounds is explored. This review also discusses the routes that have been taken to modify the profiles of primary metabolites for increasing the nutritional quality of foods as well as the production of specialized metabolites, cosmetics, pharmaceuticals and industrial chemicals. As the universe of high-value biosynthetic pathways continues to expand, and the tools to engineer these pathways continue to develop, it is likely plants and algae will become increasingly valuable for the biomanufacturing of high-value compounds.